2003
DOI: 10.1258/002221503321626429
|View full text |Cite
|
Sign up to set email alerts
|

Is the routine use of antibiotics justified in adult tonsillectomy?

Abstract: Pain and secondary haemorrhage are the commonest complications of adult tonsillectomy, occurring mostly in the community. This is a randomized, double-blind, placebo-controlled, prospective trial of the effect of perioperative amoxycillin on these complications. The incidence and severity of post-operative haemorrhage was measured. For the first 10 post-operative days patients provided a linear pain score, a record of GP visits, and their use of additional antibiotics and analgesics. Of 95 patients considered:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 16 publications
2
55
0
1
Order By: Relevance
“…O'Reilly et al [20], Lee et al [21] found no evidence of reduced secondary haemorrhage rate following routine use of prophylactic antibiotics and question the justification of using prophylactic antibiotic routinely. Dhiwakar et al [22] in their meta-analysis of ten studies in the Cochrane review found no significant reduction in post-tonsillectomy bleeding and the routine use of prophylactic antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…O'Reilly et al [20], Lee et al [21] found no evidence of reduced secondary haemorrhage rate following routine use of prophylactic antibiotics and question the justification of using prophylactic antibiotic routinely. Dhiwakar et al [22] in their meta-analysis of ten studies in the Cochrane review found no significant reduction in post-tonsillectomy bleeding and the routine use of prophylactic antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding is another frequent post-operative complication 5,7 . It was observed between the first and fifth days of post-op in 21% of the patients in the group treated with amoxicillin and in 26.8% of the patients included in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was expected that the patients' caretakers would have difficulties in properly characterizing bleeding episodes. As none of the children went to the emergency unit nor required medical intervention, it was assumed that the reported episodes were of minor bleeding (defined as bleeding episodes taking place within 24 hours or surgery and reported by the patient or caretaker requiring no specific treatment) 7 . When looking at post-adenotonsillectomy complications and the need to see a physician, Terence et al 9 found an incidence of 2-4% of secondary bleeding, a low rate as considered by the authors when compared to other studies.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of perioperative antibiotics on recovery after tonsil surgery has been investigated in tonsillectomy patients [10][11][12] . Studies performed in adults reported divergent results.…”
Section: Discussionmentioning
confidence: 99%